Modelling, Design, and Performance Comparison of Triple Gate Cylindrical and Partially Cylindrical FinFETs for Low-Power Applications. (11th December 2012) - Rai, Sanjeev; Sahu, Jyotsna; Dattatray, Wanjul; Mishra, R. A.; Tiwari, Sudarshan
Abstract : The FinFETs recently have been the rallying point for the engineers as far as the development of the technology is concerned. The authors here have tried successfully to compare the performance of 30 nm conventional triple gate (Conv) FinFET structure with that of partially cylindrical (PC) FinFET. In PC-FinFET the fin is divided into two regions. Region I is partially cylindrical and has curvature of half of the fin width, and Region II is like a conventional FinFET (having flat region). The results show that there is considerable improvement in Ion, Ioff, and subsequent suppression of short channel effects, that is, subthreshold slope, DIBL, self heating effect, and so forth. The improvement has also been felt in series resistance in PC-FinFET as compared to C-FinFET. It is noteworthy also to mention that in PC-FinFET the corner of fin is rounded thus reducing the side wall area which further reduces the gate capacitance reducing the intrinsic delay. The DC and transient analysis of CMOS inverter using C-FinFET and PC-FinFET have been done which shows that PC-FinFET inverter has reduced propagation delay as compared to C-FinFET.